Treatment outcomes of concurrent chemoradiotherapy for locally advanced sinonasal squamous cell carcinoma: A single-institution study. (2nd November 2015) - Kim, Ji Heui; Lee, Yoon Se; Chung, Yoo-Sam; Jang, Yong Ju; Kim, Sung-Bae; Lee, Sang-Wook; Lee, Bong-Jae
Abstract: Conclusions: CCRT is a potential treatment option for locally advanced sinonasal SCC in terms of organ preservation. Objectives: Concurrent chemoradiotherapy (CCRT) is increasingly used for patients with advanced head and neck cancer to preserve organ function and improve survival. In the present study, treatment outcomes were compared between surgery and post-operative radiotherapy (PORT) and CCRT in patients with locally advanced sinonasal squamous cell carcinoma (SCC). Methods: The records of 30 patients with non-metastatic stage III and IV sinonasal SCC were retrospectively reviewed. Fifteen patients were treated with CCRT and 15 patients underwent PORT. Results: The locoregional recurrence-free, distant metastasis-free, disease-free, disease-specific, and overall survival rates did not differ between PORT and CCRT groups. In addition, there were no significant differences in incidence rates of acute and chronic toxicities between the two groups.